202 COVID-19 Pandemic Sleep Disturbances Related To Dietary Behavior at the US-Mexico Border. (3rd May 2021) - Valencia, Dora; Ghani, Sadia; Delgadillo, Marcos; Madhivanan, Purnima; Krupp, Karl; Ruiz, John; Seixas, Azizi; Jean-Louis, Giardin; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The COVID-19 pandemic has disrupted life at the US-Mexico border in many ways, including sleep and dietary behavior. Given the potential long-term impact of worsening sleep and metabolic health due to the pandemic, the present study examines whether changes to dietary behavior were associated with changes to sleep. Methods: Participants were 155 individuals who completed the Nogales Cardiometabolic Health and Sleep (NOCHES) Study and were contacted about completing a COVID-19 sub-study (95% Hispanic/Latino). Participants reported the degree to which they experienced pandemic-related changes to sleep, including a more regular schedule, overall improvement, overall worsening, more initial insomnia, more middle-of-the-night insomnia, more daytime sleepiness, and more napping. They were also asked whether as a result of the pandemic they consumed an overall healthier diet, more homecooked meals, more processed meals, more regular meals, whether they enjoyed food more, and degree of overeating. Ordinal regressions with diet change as outcome and sleep change as predictor were adjusted for age, sex, education, and socioeconomics. Results: Those who reported more regular sleep were more likely to report a healthier overall diet (oOR=3.12, p<0.0005), more homecooked meals (oOR=2.18, p=0.001), more enjoyment of food (oOR=1.71, p=0.028), and less likelihood of overeating (oOR=0.59, p=0.033). Similarly, those who reported more "improved" sleep reported healthier overall diet (oOR=7.42, p<0.0005), more homecooked meals (oOR=2.59, p=0.001), more regular diet (oOR=2.15, p=0.006), more enjoyment of food (oOR=2.92, p<0.0005), less consumption of processed foods (oOR=0.54, p=0.039), and less overeating (0.33, p<0.0005). Those whose sleep worsened reported eating more processed foods (oOR=1.78, p=0.030) and overeating (oOR=3.90, p<0.0005). Those who reported more initial insomnia reported eating more processed foods (oOR=1.93, p=0.016), more regular diet (oOR=1.65, p=0.042), and overeating more often (oOR=4.11, p<0.0005). More middle-of-the-night insomnia was associated with eating more processed foods (oOR=2.45, p=0.001), more regular diet (oOR=1.66, p=0.031), and overeating more often (oOR=3.68, <0.0005). Those with more daytime sleepiness also reported eating more processed foods (oOR=2.36, p=0.003), more regular diet (oOR=1.79, =0.019), and overeating more often (oOR=3.28, p<0.0005). More napping was associated with a more regular diet (oOR=1.90, p=0.011) and more overeating (oOR=3.53, p<0.0005). Conclusion: Overall, worse sleep led to worse dietary behavior, especially eating more processed food and overeating. Support (if any): Supported by T32HL007249, R01MD011600, R01DA051321